Keadilan Distribusi dalam Ekonomi Syariah Perspektif Baqir al-Shadr - Yusriza, Yusriza; Ida Irawan, Riska; Nadia, Nadia (Economia: Journal of Economics and Management, 2024)
This study aims to analyze the concept of distributive justice in Islamic economics with a focus on the thought of Muhammad Baqir al-Sadr. The background of this research is based on the increasing inequality in wealth distribution within modern economic systems, which have not been able to achieve optimal social justice. This study employs a qualitative approach using library research, examining the major work of Baqir al-Sadr, particularly Iqtisaduna, along with relevant supporting literature. The findings indicate that the concept of distribution in the thought of Muhammad Baqir al-Sadr is not positioned as the final stage of economic activity, but rather as an integral part of the economic system’s structure. Distributive justice is understood as a proportional principle that considers individual needs, contributions, and social responsibilities. Furthermore, distribution is realized through the integration of ownership structures, Islamic instruments such as zakat and waqf, and the role of the state in maintaining economic balance. This approach is not only corrective in addressing inequality but also preventive in avoiding the concentration of wealth. Thus, Baqir al-Sadr’s thought offers a comprehensive conceptual framework for achieving distributive justice and remains relevant in addressing contemporary economic challenges. Abstrak Penelitian ini bertujuan untuk menganalisis konsep keadilan distribusi dalam ekonomi syariah dengan fokus pada pemikiran Muhammad Baqir al-Sadr. Latar belakang penelitian ini didasarkan pada meningkatnya ketimpangan distribusi kekayaan dalam sistem ekonomi modern yang belum mampu menghadirkan keadilan sosial secara optimal. Penelitian ini menggunakan pendekatan kualitatif dengan jenis kajian pustaka (library research), dengan mengkaji karya utama Baqir Shadr, khususnya Iqtisaduna, serta berbagai literatur pendukung yang relevan. Hasil penelitian menunjukkan bahwa konsep distribusi dalam pemikiran Muhammad Baqir al-Sadr tidak diposisikan sebagai tahap akhir dari proses ekonomi, melainkan sebagai bagian integral dari struktur sistem ekonomi Islam. Keadilan distribusi dipahami sebagai prinsip proporsional yang mempertimbangkan kebutuhan, kontribusi, dan tanggung jawab sosial individu. Selain itu, distribusi diwujudkan melalui integrasi antara struktur kepemilikan, instrumen syariah seperti zakat dan wakaf, serta peran negara dalam menjaga keseimbangan ekonomi. Pendekatan ini tidak hanya bersifat korektif terhadap ketimpangan, tetapi juga preventif dalam mencegah konsentrasi kekayaan. Dengan demikian, pemikiran Baqir Shadr menawarkan kerangka konseptual yang komprehensif dalam mewujudkan keadilan distribusi dan memiliki relevansi dalam menjawab tantangan ekonomi kontemporer.